A PPh3-catalyzed sequential annulation reaction to construct cyclopentane-fused dihydropyrazolone-pyrrolidinediones. Issue 29 (14th July 2020) - Cheng, Cheng; Sun, Xiaobin; Miao, Zhiwei
Abstract : An effective strategy for the synthesis of cyclopentane-fused dihydropyrazolone-pyrrolidinediones via a PPh3 -catalyzed sequential annulation reaction of maleimides and unsaturated pyrazolones has been developed. Abstract : A PPh3 -catalyzed sequential cycloaddition of maleimides with unsaturated pyrazolones has been developed. This protocol provides a simple and practical strategy for the construction of dispirocyclopentyl-[dihydropyrazolone-pyrrolidinedione] pyrrolidinedione skeletons containing five contiguous stereogenic centers, including two spiro-quaternary centers, with moderate yields (34–73%) and excellent diastereoselectivities (>20 : 1).